Особливості медико-психолого-педагогічного супроводу інклюзивної освіти дошкільників, які потребують корекції психофізичного розвитку - Кузава, Ірина Борисівна; Kuzava, Iryna B. (Черкаський національний університет імені Богдана Хмельницького, 2013)
У науковій статті на основі узагальнення наукових джерел розкриваються особливості медико-психолого-педагогічного супроводу інклюзивної освіти дітей дошкільного віку, які потребують корекції психофізичного розвитку. Визначено сутність, зміст, компоненти і принципи медико-психолого-педагогічного супроводу. The introduction of the idea of inclusive education needs rethinking existing models of general and special system of preschool education and building on this basis the corresponding system of medical, psychological and educational assistance to students with mental and physical disabilities, which should contribute to their full participation in a general area. Because scientific article based on a synthesis of scientific sources regarding medical, psychological and educational support preschool children who require correction of psychophysical development in inclusive education. The character, scope, components and principles of medical, psychological and pedagogical support inclusive education. In particular, the theoretical study investigated problem give us grounds for etermining medical, psychological and pedagogical support system as educational activities designed to create a comprehensive system of clinical and psychological, psycho-educational and psychotherapeutic environment conducive to learning and skills, successful adaptation Rehabilitation, personal identity formation, normalization of family relationships, its integration into the society.
Particularly medical and psycho-pedagogical support inclusive education preschoolers in need of correction psychophysical development.
докторант кафедри психокорекційної педагогіки НПУ ім. М. П. Драгоманова (м. Київ) кандидат педагогічних наук, доцент
Keywords: супровід; медико-психолого-педагогічний супровід; інклюзивна освіта; дошкільники, які потребують корекції психофізичного розвитку; депривація; фрустрація; соціальна компетентність; accompaniment; medical, psychological and pedagogical support; inclusive education; preschooler; requiring correction psychophysical development; deprivation; frustration; social competence